Positivity and stabilization of fractional 2D linear systems described by the roesser model - Kaczorek, Tadeusz (1932- ); Rogowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
A new class of fractional 2D linear discrete-time systems is introduced. The fractional difference definition is applied toeach dimension of a 2D Roesser model. Solutions of these systems are derived using a 2D Z-transform. The classicalCayley-Hamilton theorem is extended to 2D fractional systems described by the Roesser model. Necessary and sufficientconditions for the positivity and stabilization by the state-feedback of fractional 2D linear systems are established. Aprocedure for the computation of a gain matrix is proposed and illustrated by a numerical example.
Keywords: positivity; stabilization; fractional systems; Roesser model; 2D systems